Disentangling the mechanisms sustaining a stable state of submerged macrophyte dominance against free-floating competitors - Szabó, Sándor; Koleszár, Gergő; Zavanyi, Györgyi; Nagy, Péter Tamás; Braun, Mihály; Hilt, Sabine (Frontiers in Plant Science, 2022)
Free-floating and rootless submerged macrophytes are typical, mutually exclusive vegetation types that can alternatively dominate in stagnant and slow flowing inland water bodies. A dominance of free-floating plants has been associated with a lower number of aquatic ecosystem services and can be explained by shading of rootless submerged macrophytes. Vice versa, high pH and competition for several nutrients have been proposed to explain the dominance of rootless submerged macrophytes. Here, we performed co-culture experiments to disentangle the influence of limitation by different nutrients, by pH effects and by allelopathy in sustaining the dominance of rootless submerged macrophytes. Specifically, we compared the effects of nitrogen (N), phosphorus (P), iron (Fe) and manganese (Mn) deficiencies and an increased pH from 7 to 10 in reducing the growth of free-floating Lemna gibba by the rootless Ceratophyllum demersum. These macrophyte species are among the most common in highly eutrophic, temperate water bodies and known to mutually exclude each other. After co-culture experiments, additions of nutrients and pH neutralisation removed the growth inhibition of free-floating plants. Among the experimentally tested factors significantly inhibiting the growth of L. gibba, an increase in pH had the strongest effect, followed by depletion of P, N and Fe. Additional field monitoring data revealed that in water bodies dominated by C. demersum, orthophosphate concentrations were usually sufficient for optimal growth of free-floating plants. However, pH was high and dissolved inorganic N concentrations far below levels required for optimal growth. Low N concentrations and alkaline pH generated by dense C. demersum stands are thus key factors sustaining the stable dominance of rootless submerged vegetation against free-floating plants. Consequently, N loading from e.g. agricultural runoff, groundwater or stormwater is assumed to trigger regime shifts to a dominance of free-floating plants and associated losses in ecosystem services.